Sosialisasi Pemilahan Sampah dan Redesain Tempat Sampah Sesuai Klasifikasinya - Lina Yuliana; Julian Yofi Limbong (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
The volume of waste in Balikpapan City is estimated to reach 380 to 420tons per day. Currently, A Landfill Site in Manggar District area is approaching overcapacity. The government estimates that landfill area will only last until 2026. To help reduce waste, residents RT 50 PJHI – Batakan has several useful activities. One of the useful activities is the activities of the waste, used goods and coin donation movement (GADIS JELITAKU). This activity utilizes plastic waste, paper, organic waste, leftover cooking oil and coins to be recycled into goods that have a price or economics value. However, the provision of public facilities both in terms of cleanliness, health and safety is still lacking. Cleaning facilities or trash cans that are no longer suitable for use in the area will be replaced with trash bins with the addition of 3 categories of waste segregation. With the reconditioning or redesign of this new trash can, it hoped that it can increase residents awareness of the importance of maintaining a clean and healthy environment and increase the level of creativity and innovation in utilizing waste.